Resource rents, universal basic income, and poverty among Alaska's Indigenous peoples. (June 2018) - Berman, Matthew
Highlights: The Alaska Permanent Fund Dividend (PFD) has provided UBI averaging $6600 US (2015) dollars for a family of four since 1982. The PFD reduced the number of rural Alaska Indigenous people in poverty during 2011–2015 by 22%, down from 46% in 2000. The PFD reduced poverty among rural Alaska Indigenous seniors by more than 40%, to rates that are now relatively low. Child poverty rates have been increasing; however, the PFD reduced 2011–2015 rural Alaska Native child poverty rates by 25%. Errors in official statistics will cause them to understate the actual rise in poverty rates as future PFD amounts decline. Abstract: The Alaska Permanent Fund Dividend (PFD) program provides universal basic income (UBI) to all residents from investment earnings of a state sovereign wealth fund created from oil rents. This paper evaluates the effect of the PFD to mitigate poverty among the state's rural Indigenous (Alaska Native) peoples: a population with historically high poverty rates living in a region with limited economic opportunities. Errors in recording PFD income in data used to calculate official poverty statistics cause them to misrepresent poverty in Alaska and understate the effect of the PFD. Estimating poverty rates with and without PFD income therefore requires reconstruction of family incomes from household-level data. Estimated poverty rates from reconstructed income show that the PFD has had a substantial, although diminishing mitigating effect on poverty for rural Indigenous families. The PFD has had a larger effect on poverty among children and elders than for the rural Alaska Native population as a whole. Alaska Native seniors, who receive additional sources of UBI derived primarily from resource rents besides the PFD, have seen a decline in poverty rates, while poverty rates for children have increased. Evidence has not appeared for commonly hypothesized potential adverse social and economic consequences of UBI.